The war of the worlds - Wells, H. G. (Oxford University Press, 1972)
The Oxford Progressive English readers series provides a wide range of reading for loaners of English. It incudes classics, the favourite stories of young readers, and also the modern fiction.Grade at 1400-2100-3100 and 3700 word level.